Characterization and solubilization of bitter-responsive receptors that couple to gustducin - Ming, Ding (The National Academy of Sciences, 1998)
The tastes of many bitter and sweet compounds are thought to be transduced via guanine nucleotide binding protein (G-protein)-coupled receptors, although the biochemical nature of these receptors is poorly understood at present. Gustducin, a taste-specific G-protein closely related to the transducins, is a key component in transducing the responses to compounds that humans equate with bitter and sweet. Rod transducin, which is also expressed in taste receptor cells, can be activated by the bitter compound denatonium in the presence of bovine taste membranes. In this paper, we show that gustducin is expressed in bovine taste tissue and that both gustducin and transducin, in the presence of bovine taste membranes, can be activated specifically by several bitter compounds, including denatonium, quinine, and strychnine. We also demonstrate that the activation in response to denatonium of gustducin by presumptive bitter-responsive receptors present in taste membranes depends on an interaction with the C terminus of gustducin and requires G-protein βγ subunits to provide the receptor-interacting heterotrimer. The taste receptor–gustducin interaction can be competitively inhibited by peptides derived from the sites of interaction of rhodopsin and transducin. Finally, as the initial step toward purifying taste receptors, we have solubilized this bitter-responsive taste receptor and maintained its biological activity.